The importance of the teacher of physical education in the childish development - Costa, Jefferson Martins; Martins, Karina Vieira; Nunes, Gabriel Pereira; Claudino, Guilherme dos Santos (ARCHIVES OF HEALTH INVESTIGATION, 2018)
With the intent to show the importance to accompany the development psychomotor of the boy from the first stages of life, the present article looks for to emphasize the big relevance is the participation of the teacher of Physical Education in the Childish Education. In this sense the text finds divided in three stages: the introduce on, which aimed our general and specific aims in relation to the study realized, like this as the authors that evidence the value of this professional in the side dish of boys of 0-5 years of age; the development will highlight the main points of the process of education and learning of the physical education, with the side dish of professional properly enabled in consonance with the polyvalent teacher and also, show the municipalities that already regulated laws that force the presence of such professional and, at last, the final considerations, where we report the failures of the Universities in giving the owed relevance for this area inside the graduation in Pedagogy. Descriptors: Faculty; Physical Education and Training; Child Rearing; Psychomotor Performance.